الوقف المؤقت للمقابر: دراسة فقهية مقارنة بقوانين الوقف الإماراتية - الحناوي، أمجد; سليمان، محمد سليمان النور (جامعة بن يوسف بن خدة الجزائر 1 - كلية العلوم الإسلامية - مخبر الشريعة, 2023)
لقد اعتنى البحث بدراسة نوع من أنواع الوقف المؤقت وهو وقف المقابر من خلال تعريفه ومشروعيته، وعوائده، وأحكامه، وضوابطه، مع مقارنة ذلك بما أخذت به قوانين الوقف الإماراتية. وقد نهج الباحث في بحثه المنهج الاستقرائي التحليلي المقارن، من خلال استقراء النصوص الدالة على وقف المقابر، ومن ثم تحليلها تحليلا علمياً دقيقاً لاستخراج الأحكام المتعلقة به، والضوابط التي يرتكز عليها، مع بيان رأي الفقه الإسلامي في ذلك، ومن ثم مقارنة هذا الرأي بما أخذت به قوانين الوقف الإماراتية. وقد توصل الباحث إلى مجموعة من النتائج من أبرزها: أن وقف المقابر المؤقت يحكمه ضابطان، هما: تيقن بلاء الميت والتأكد من ذلك من أهل الخبرة، ومراعاة اختلاف المدة الزمنية لبلاء الميت من بلد لآخر، وأن قوانين الوقف الإماراتية أخذت بمذهب المالكية في جواز الوقف المؤقت، لكنها نصت على عدم جواز وقف المقابر إلا بشكل مؤبد. The research aims to study a type of temporary endowment, which is the endowment of cemeteries through its definition, legality, returns, rules, and regulations, with a comparison of that with the UAE endowment laws. In his research, the researcher used the inductive, analytical and comparative approach, by extrapolating the texts indicating the endowment of graves, and then analyzing them in a scientific and accurate analysis to extract the rulings related to it, and the controls on which it is based, with a statement of the opinion of Islamic jurisprudence in that, and then comparing this opinion with what was taken by UAE endowment laws. The researcher concluded a set of results, the most important of which are: that the temporary endowment of cemeteries is governed by two rules: Certainty of death as affirmed by experts considering the difference in the time period of the affliction of the dead from one country to another, and that the Emirati endowment laws adopted the Maliki doctrine in the permissibility of a temporary endowment, but they stipulated that it is not permissible to endow the graves except in a permanent manner.
Keywords: الفقه الإسلامي -- الشريعة الإسلامية -- المذهب المالكي -- وقف المقابر